BS ISO 3951-1. Sampling procedures for inspection by variables. Part 1. Specification for single sampling plans indexed by acceptance quality limit (AQL) for lot-by-lot inspection for a single quality characteristic and a single AQL (6th May 2021) - British Standards Institution,
No abstract available